Projeto e prototipagem de um dinamômetro elétrico de bancada de baixo custo aplicado a ensaios em motores de combustão interna - Rogério Lucas dos Santos Rosa (2019)
The methodology used for testing internal combustion engines it is in constantly evolution compared to the equipment used to evaluate nineteenth century steam engines. Today's engine dynamometers use friction braking systems (such as Prony's brake), hydraulic dynamometers, or electric dynamometers. However, it is still necessary to advance these equipments with respect to performing transient tests, speed control, torque measurement and test time minimization. The present work has as its general objective the design and development of a low cost ac dynamometer applied to low power engine tests benches. In addition, this project also aims to develop a system capable of performing direct torque measurement in place of the conventional strain gauge system based on the stress and strain relationship. It was used a threephase induction motor driven by a unidirectional two-phase three-phase converter (frequency inverter) operating with vector control. This dynamometer will be used in both operating conditions as both engine (unloaded test) and generator (load test). The data acquisition system developed reads the signals from the dynamometric bench, the digital conversion and the display of the curves in a graphical interface. Static testing is conducted on a 7.5 kW @ 4200 rpm single-cylinder motor, for different load values, and the results are compared to datasheet curve.